Potenciales evocados II: potenciales exógenos - Muñoz Gamboa, Caupolicán; Jiménez Cruz, Joel (Revista Mexicana de Ingenieria Biomedica, 2002)
We present a particular type of evoked potentials, known as exogen, which is the direct product of a controlled sensorial stimulus. We analyze their physiological origins, we describe different types of stimulations for each of them, we specify their morphology, their main characteristics and properties. At the same time, we detail some of their more common clinical applications.